Reforming the Tort Reform Agenda - Julie Davies (Washington University Journal of Law & Policy, 2007)
Although the current longstanding impasse over the U.S. health care system in general and the 46.6 million uninsured Americans in particular is no game, a reshuffling of the issues may open an opportunity to solve what seems to be an intractable problem. To date, it seems every political solution has been tried and has failed. In this Article, I argue that one way to gain political traction on the problem is to integrate the health care issue into the agenda for tort reform. At first blush, the issues may seem disconnected: recovery through the tort system is admittedly a narrower issue than health care access, affecting only those injured through tortious conduct of others. However, closer examination reveals connections between these topics as yet unrecognized by the groups with the strongest interests in them. Through a reshuffling that reveals these links and harnesses the political capital in the tort reform movement, the powerful interest groups that comprise the stakeholders in both debates may realize new benefits through solving the problems created by the inaccessibility of health care for the uninsured. At the same time, resolution of this issue may make it easier to effectuate changes that lower the costs of the tort system.
Keywords: Government policy; Tort reform; Health care reform; Social justice; Health care services accessibility; Health insurance; United States